Pharmacotherapy of Depressive Disorders in Conditions of Coronavirus Disease: Pharmacoeconomic Experimental Study - Shapovalova, Viktoriia (SSP Modern Pharmacy and Medicine, 2023)
Purpose of the study was to conduct comprehensive pharmacoeconomic, clinical and pharmacological, marketing, documentary, normative and legal studies of pharmacotherapy of depressive disorders during global coronavirus pandemic. Pharmacoeconomic methods of analysis, in particular ABC/VEN analysis were used to select effective and safe drugs of pharmacotherapy of depression. According to the results of the ABC cost analysis, drugs for the pharmacotherapy of depression were distributed in descending order of their cost: group A (most expensive) includes drugs whose pharmacotherapy costs were equal to 81.76% of total costs; to group B (average cost) – 14.21%, and to group C (cheapest) – 4.03%. Group A included 10 INN drugs (including Citaloprame, Olanzapine, Fluvoxamine), the cost of one dose was 4956.5 UAH, which accounted for 81.76% of the total cost of pharmacotherapy for depression. Group B included four INNs (Sertraline, Escitaloprame, Mianserine, Sulpiride), the total cost of one dose of which was 861.3 UAH (14.21%). As part of group C – four INN (Doxepine, Lithium, Fluoxetine, Amitriptyline), the cost – 244.54 UAH per dose (4.03%). According to VEN analysis, it was experimentally proven that the highest costs of pharmacotherapy of depression were 77.7% for drugs of category V (vital) and 22.3% for drugs of category E (essential). During the VEN analysis it was found that fourteen INN drugs are included in category V (Vital). Category E includes four INNs. No INNs were included into category N (Non-Essential). The obtained results made it possible to make administrative and managerial decisions in determining the pharmacotherapy of patients with depressive disorders.